Polypyrrole doped with dodecylbenzene sulfonate as a protective coating for copper. (20th November 2018) - Carragher, Ursula; Breslin, Carmel B.
Abstract: Polypyrrole doped with dodecylbenzene sulfonate (DBS) was formed at copper, PPy–DBS, and at a thin coating of polypyrrole doped with tartrate to form a bilayer of PPy–Tar/PPy–DBS at copper. The two polymer coatings showed good protective properties. Breakdown potentials of 0.85 V and 0.93 V vs SCE were recorded in 0.1 M NaCl for the PPy–DBS and PPy–Tar/PPy–DBS bilayer, respectively. The more protective properties of the bilayer were explained in terms of an adherent thin polymer that was formed in the tartrate solution without significant dissolution of copper before the polymer was nucleated. The protective properties were also evident from open-circuit potential measurements where the potential adopted by the polymer coated copper remained constant and higher than the potential of the uncoated copper for several days. Furthermore, a decrease in the corrosion current density was observed from 1.95 μA cm −2 for copper to 0.12 μA cm −2 for the bilayer. The concentration of DBS had an influence on the properties of the polymer films with more protective films formed in 0.05 M DBS. The critical micelle concentration of DBS in 0.3 M pyrrole was measured as 9.8 mM, indicating a relatively high level of micelles in 0.05 M DBS. The protective properties of the coating were attributed to the large and immobile DBS anion, which gives the polymer cation exchange properties, minimising the uptake of chloride anions. In addition, the incorporation of anionic micelles may occur to repel further the chloride anions.